2002
DOI: 10.1364/ao.41.005792
|View full text |Cite
|
Sign up to set email alerts
|

Light-scattering properties of plate and column ice crystals generated in a laboratory cold chamber

Abstract: Angular scattering properties of ice crystal particles generated in a laboratory cloud chamber are measured with a lightweight polar nephelometer with a diode laser beam. This cloud chamber produces distinct plate and hollow column ice crystal types for light-scattering experiments and provides a controlled test bed for comparison with results computed from theory. Ice clouds composed predominantly of plates and hollow columns generated noticeable 22 degrees and 46 degrees halo patterns, which are predicted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…Case A data (non-halo case) represented by red symbols are distributed over a smaller MVD range (< 130 µm) and with sizes larger than 20 µm. This size appears to delineate the lower limit of ice crystal size responsible (at visible wavelengths) for halo formation according to earlier laboratory studies (Sassen and Liou, 1979;Barkey et al, 2002) and theoretical results (Mishchenko and Macke, 1999). In situ observations at the South Pole station (Shcherbakov et al, 2006a;Lawson et al, 2006) also reported very well-marked 22 • halo peaks with pristine ice crystals no larger than 100 µm.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Case A data (non-halo case) represented by red symbols are distributed over a smaller MVD range (< 130 µm) and with sizes larger than 20 µm. This size appears to delineate the lower limit of ice crystal size responsible (at visible wavelengths) for halo formation according to earlier laboratory studies (Sassen and Liou, 1979;Barkey et al, 2002) and theoretical results (Mishchenko and Macke, 1999). In situ observations at the South Pole station (Shcherbakov et al, 2006a;Lawson et al, 2006) also reported very well-marked 22 • halo peaks with pristine ice crystals no larger than 100 µm.…”
Section: Discussionsupporting
confidence: 81%
“…Observations of cloud ice particles tend to show much smoother scattering behaviour compared with modelling results obtained in laboratory studies (Sassen and Liou, 1979;Crépel et al, 1997;Barkey et al, 2002). The first in situ observations of azimuthal scattering patterns also confirmed that smooth scattering phase functions prevail in cirrus clouds Auriol et al, 2001;Field et al, 2003a;Gayet et al, 2004;Baumgardner et al, 2005). Defaults in crystal geometry, roughness of the ice surface or imperfect internal structure are known to hamper the formation of halos (see among others Baran and Labonnote, 2007).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The HG phase function is very smooth, while that of spheres features icebow and glory peaks not seen for real snow along with very low sideward scattering. Based on a comparison of a few shape models with phase function measurements for laboratory-generated ice crystals (Barkey et al, 2002), Kokhanovsky and Zege (2004) recommended, instead of spheres, the use of Gaussian random spheres (Muinonen et al, 1996;Nousiainen and Muinonen, 1999) or Koch fractals (Macke et al, 1996), which both exhibit a relatively featureless phase function. Since Gaussian random spheres have several free parameters while Koch fractals have none (except for the degree of distortion for randomized Koch fractals), Koch fractals were selected by Kokhanovsky and Zege (2004).…”
Section: P Räisänen Et Al: Parameterization Of Single-scattering Prmentioning
confidence: 99%
“…On one hand, snow strongly reflects UV light, and plants, which absorb it, are therefore expected to show up in high contrast against the light (UV-reflecting) background. Where plants are closely surrounded by or even partially covered with snow, however, heterogeneous angular scattering of UV off randomly orientated snow crystals (Barkey et al, 2002;Kokhanovsky and Zege, 2004;Shcherbakov et al, 2006) potentially reduces this contrast. This possibility raises the question of how diminutive Arctic plants lying in the snow where Rangifer feed (Pruitt, 1959;LaPerriere and Lent, 1977;Skogland, 1978) appear under natural UV illumination.…”
Section: Introductionmentioning
confidence: 99%